2009
DOI: 10.1016/j.cell.2009.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The IFITM Proteins Mediate Cellular Resistance to Influenza A H1N1 Virus, West Nile Virus, and Dengue Virus

Abstract: Summary Influenza viruses exploit host cell machinery to replicate, resulting in epidemics of respiratory illness. In turn, the host expresses anti-viral restriction factors to defend against infection. To find host-cell modifiers of influenza A H1N1 viral infection, we used a functional genomic screen and identified over 120 influenza A virus-dependency factors with roles in endosomal acidification, vesicular trafficking, mitochondrial metabolism and RNA splicing. We discovered that the interferon-inducible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

98
1,515
3
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,135 publications
(1,632 citation statements)
references
References 43 publications
98
1,515
3
16
Order By: Relevance
“…Multiple siRNA screens for influenza virus, an NS RNA virus that replicates in the nucleus, have identified COPI, but not COPII, as required for infection (11,12,24). Although COPI is required for influenza as well as VSV G-mediated virus entry (12), our results for VSV are in contrast to these studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Multiple siRNA screens for influenza virus, an NS RNA virus that replicates in the nucleus, have identified COPI, but not COPII, as required for infection (11,12,24). Although COPI is required for influenza as well as VSV G-mediated virus entry (12), our results for VSV are in contrast to these studies.…”
Section: Discussioncontrasting
confidence: 56%
“…The advent of siRNA technology and the availability of genome-wide siRNA libraries have been useful in identifying host factors required for influenza virus, an NS RNA virus, and several positive-strand RNA viruses, as well as HIV (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The lack of similar studies with other NS RNA viruses has limited the understanding of the role of host cell factors in replication of these viruses.…”
mentioning
confidence: 99%
“…Gene-knockout studies, however, revealed that neither Fragilis nor Stella is essential for PGC specification (Payer et al 2003;Lange et al 2008). Instead, Stella has been found to be a critical factor to protect the maternal genome and paternally imprinted genes from genome-wide DNA demethylation that occurs in the zygotes (Nakamura et al 2007), whereas Fragilis has a critical function in restricting the replication of multiple pathogenic viruses including influenza (Brass et al 2009;Everitt et al 2012).…”
mentioning
confidence: 99%
“…Un effet des IFITM sur le virus de la grippe, le virus du Nil occidental (ou West Nile virus) et celui de la dengue, a été initialement décrit en 2009 par Abraham Brass par un criblage d'ARN interférence [2]. L'action antivirale des IFITM, consistant en une inhibition de la réplication virale, peut se produire de deux manières différentes.…”
Section: Les Protéines Ifitmunclassified
“…Puisque l'activité antivirale d'IFITM3 est en partie proportionnelle au niveau de son accumulation dans la cellule, toute modification post-traductionnelle, pouvant moduler la quantité ou la stabilité d'IFITM3 au sein de la cellule, aura donc potentiellement une répercussion sur sa capacité antivirale. En conséquence, l'identification de l'ubiquitine ligase, responsable in fine de la dégradation d'IFITM3, apparaît donc comme une étape cruciale qui 2 Tyrosine-Acide glutamique-Méthionine-Leucine. 3 Phospho-transférase spécifique de la tyrosine, appartenant à la famille des tyrosine protéine kinases Src, principalement localisée au niveau de la membrane plasmique et participant à la régulation de plusieurs voies de signalisation.…”
Section: Les Protéines Ifitmunclassified